Nasobiliary Drain Diverted through a Percutaneous Endoscopic Gastrostomy Tube: A Novel Approach to Nasobiliary Drainage - Nikolaos Dimitrios Pantzaris (Karger Publishers, 2021)
Intractable pruritus is a common, debilitating symptom and a well-defined entity occurring in chronic cholestatic disorders. Treatment options include cholestyramine, rifampicin, naltrexone, gabapentin, and sertraline, as well as more interventional measures, such as plasmapheresis, extracorporeal albumin dialysis, nasobiliary drains (NBDs), and UVB phototherapy in patients who fail to respond to medical therapy. Despite the limited data, NBD seems to be a highly effective treatment in the relief of refractory cholestatic pruritus. In this article, we present the case of a 73-year-old woman with primary biliary cholangitis and intractable pruritus, refractory to medical treatment. The patient had a complete resolution of her symptoms following an NBD placement, in which, with a novel approach, the nasal end was redirected and exited through a percutaneous endoscopic gastrostomy port, significantly improving her quality of life.